Control strategy of DFIG in hybrid micro‐grid using sliding mode frequency controller and observer. Issue 11 (24th April 2018) - Fu, Yang; Zhang, Hengyi; Mi, Yang; Huang, Lingling; Li, Zhenkun; Wang, Jianhui
Abstract : A doubly fed‐induction generator (DFIG) has a significant advantage of fast dynamic frequency regulation. However, conventional virtual inertia control (VIC) design only takes frequency into account and may face secondary frequency drop during rotor speed restoration. To solve these problems, the novel decentralised control strategy is proposed for a hybrid micro‐grid. Firstly, the load disturbance is considered to enhance control system accuracy, which is estimated by using the state observer based on the dynamic mathematical model. Then, the sliding mode VIC controller is designed by taking advantage of the observed disturbance value and frequency deviation for DFIG output dynamic adjustment according to the conventional frequency control (VIC) model. Furthermore, during DFIG rotor speed restoration, pitch angle control based on the mathematical model is applied for reserve capacity, and a new triggering condition according to the conventional condition is designed, so as to release reserve power at an appropriate time. Finally, the proposed strategy is tested in a typically isolated micro‐grid with diesel and DFIG through a simulation and experiment.